Climate change and health reference manual, 2012. - World Health Organization (Manila Department of Health & World Health Organization, 2012)
The primary objective of this manual is to enhance current understanding of local health professionals of the associations and implications of climate change on human health.
Module 1: Science of climate change -- Module 2: Threats, vulnerability and impacts of climate change -- Module 3: Climate change initiatives and adaptation strategies -- Module 4: Planning on climate change and health.
Includes bibliographical references (pages 107-120)
Keywords: Climatic changes -- Health aspects -- Philippines -- Handbooks, manuals, etc; Medical climatology -- Philippines -- Handbooks, manuals, etc; Human beings--Effect of climate on -- Philippines -- Handbooks, manuals, etc; Environmental health -- Philippines -- Handbooks, manuals, etc